Optimization of process parameters on color strength and antimicrobial activities of cotton fabric dyed with Rubia cordifolia extract. Issue 7 (3rd July 2022) - Boominathan, Senthilkumar; V, Karthi; Balakrishanan, Senthilkumar
ABSTRACT: The present study aims at optimization of dyeing process parameters such as dyeing temperature, dyeing pH, and mordant concentration toward achieving maximum color strength and antimicrobial activity of cotton fabric dyed with Indian madder ( Rubia cordifolia ) as a natural dye. Box-Behnken three factorial with three levels experimental design (dyeing temperature ranges are 60ºC, 70ºC, and 80ºC, dyeing pH ranges are 6, 9, and 12, Mordant concentration ranges are 10%, 20%, and 30% of OWF) was used for optimization. Results showed that all the selected process variables have influenced the color strength as well as antimicrobial activity against the microbes such as Staphylococcus aureus and Escherichia coli . The quadratic regression models have been developed for optimization of all the process parameters and it was validated through ANOVA. UV-Vis spectroscopy, Phytochemical analysis, and FTIR studies have been conducted to confirm the presence of the phytochemical compounds.